Airborne Electromagnetic Bathymetry Methods for Mapping Shallow Water Sea Depths - Vrbancich, Julian (The International Hydrographic Review, 2004)
The Airborne ElectroMagnetic Bathymetry (AEMB) method is an emerging technique for estimating the sea depth and the seawater and sea bed electrical conductivities from the ElectroMagnetic (EM) response of the shallow water marine environment. The EM response is not affected by water turbidity and therefore the AEMB method can be used for bathymetric mapping in turbid waters. AEMB measurements can be taken from fixed-wing and helicopter systems for hydrographic reconnaissance and rapid environmental assessment. I review the basic principles of airborne electromagnetic systems that have been used for bathymetric mapping and present some examples of AEMB surveys in Australian waters.